Application of Probiotics to Enhance Stress Resistance and Growth of Vannamei Shrimp (Litopenaeus vannamei) in Zero Salinity Conditions (Agrikan Jurnal Agribisnis Perikanan, 2024)
Vannamei shrimp (Litopenaeus vannamei) aquaculture faces challenges due to environmental stress, which affects growth and survival. This study aimed to evaluate the effect of probiotic supplementation on the cumulative stress index (CSI) and growth performance of vaname shrimp cultured under zero salinity conditions. A completely randomized design was employed with four treatments, each replicated three times: Treatment A (Commercial Feed (Control)); Treatment B (Commercial Feed + Probiotic 10 ml/kg); Treatment C (Commercial Feed + Probiotic 20 ml/kg); and Treatment D (Commercial Feed + Probiotic 30 ml/kg). CSI and absolute weight growth were observed after 10 days of cultivation. Water quality parameters were monitored throughout the study. The results indicated that Treatment B (10 ml/kg probiotics) yielded the lowest CSI value (30), reflecting the highest stress tolerance, followed by Treatment C (39), Treatment D (68), and the control group (85). Furthermore, Treatment B produced the highest absolute weight growth (38.6 grams), significantly outperforming other treatments. Statistical analysis showed a significant effect of probiotic supplementation on growth performance (p < 0.05) but no significant effect on survival rate (p > 0.05). Probiotic supplementation was proven effective in reducing stress and improving digestive efficiency in shrimp, thereby supporting better growth. These findings highlight the potential of probiotics, particularly at a dose of 10 ml/kg, as a sustainable approach to enhancing shrimp aquaculture performance under challenging environmental conditions.
Keywords: Vaname Shrimp; Probiotic; Cumulative Stress Indeks; Growth Performance; Salinity